Input attributes optimization using the feasibility of genetic nature inspired algorithm: Application of river flow forecasting - Afan H.A.; Allawi M.F.; El-Shafie A.; Yaseen Z.M.; Ahmed A.N.; Malek M.A.; Koting S.B.; Salih S.Q.; Mohtar W.H.M.W.; Lai S.H.; Sefelnasr A.; Sherif M.; et al. (Nature Research, 2023)
article; feasibility study; forecasting; genetic algorithm; radial basis function neural network; river; time series analysis